Is auditing the new evaluation? Can it be? Should it be?. Issue 6 (4th June 2018) - Pierre, Jon; Peters, B. Guy; de Fine Licht, Jenny
Abstract : Purpose: The purpose of this paper is to study the changing relationship between auditing and evaluation. Over the past several years, supreme auditing institutions (SAIs) in a number of advanced democracies have evolved from conventional auditing institutions to becoming increasingly concerned with assisting policy change and administrative reform in the public sector; tasks that are traditionally associated with evaluation. The paper discusses the potential consequences of this development for the SAIs themselves as well as for the audited and reforming institutions and for policy-making. Design/methodology/approach: The paper uses qualitative method and draws on the extensive literature on auditing and evaluation. The analysis has also benefitted from the authors' recent comparative research on SAIs. Findings: The findings, summarized in six points, are that the growth of auditing in areas previously assigned to evaluators, has led to a shortened time perspective; stronger emphasis on the administration of policies; increased focus on efficiency of the audited entity; greater independence from the evaluated organizations; a shift in receiver of information toward the legislature and/or the public; and improved communication. Practical implications: Evaluation as a professional and scholarly field has developed theories and advanced methods to assess the effectiveness of public programs. The growth of auditing may thus change the focus and quality of policy evaluation. Originality/value: The paper speaks to both scholars and practitioners. To the best of the knowledge a similar analysis has not been done before.